1998
DOI: 10.1182/blood.v91.11.4028.411a45_4028_4037
|View full text |Cite
|
Sign up to set email alerts
|

The Partner Gene of AML1 in t(16;21) Myeloid Malignancies Is a Novel Member of the MTG8(ETO) Family

Abstract: The t(16;21)(q24;q22) translocation is a rare but recurrent chromosomal abnormality associated with therapy-related myeloid malignancies and a variant of the t(8;21) translocation in which theAML1 gene on chromosome 21 is rearranged. Here we report the molecular definition of this chromosomal aberration in four patients. We cloned cDNAs from the leukemic cells of a patient carrying t(16;21) by the reverse transcription polymerase chain reaction using anAML1-specific primer. The structural analysis of the cDNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 44 publications
1
65
0
Order By: Relevance
“…The proliferation-associated cluster (#6) contains the protooncogene c-Myb, discussed above, and a number of other genes involved in the pathogenesis of leukemia through translocations and/or overexpression, including Runx1 [57], Scl [58], Calreticulin [59], Gata2 [60], and ETO2 [61], which is highly related to ETO, the founding member of the ETO gene family, and is a partner of AML1/Runx1 in the common t(8;21) translocation in AML. ETO2 itself has also been found to form a translocation fusion product with AML1 in therapy-induced t(16;21) myeloid leukemias; it may affect transcription of several target genes via interaction with the corepressor N-CoR.…”
Section: Novel Regulators Of Myeloid Proliferation and Self-renewalmentioning
confidence: 99%
“…The proliferation-associated cluster (#6) contains the protooncogene c-Myb, discussed above, and a number of other genes involved in the pathogenesis of leukemia through translocations and/or overexpression, including Runx1 [57], Scl [58], Calreticulin [59], Gata2 [60], and ETO2 [61], which is highly related to ETO, the founding member of the ETO gene family, and is a partner of AML1/Runx1 in the common t(8;21) translocation in AML. ETO2 itself has also been found to form a translocation fusion product with AML1 in therapy-induced t(16;21) myeloid leukemias; it may affect transcription of several target genes via interaction with the corepressor N-CoR.…”
Section: Novel Regulators Of Myeloid Proliferation and Self-renewalmentioning
confidence: 99%
“…Initial sequence analysis demonstrated that ETO is the mammalian homologue of the Drosophila gene nervy (Feinstein et al, 1995), and subsequent work has identi®ed two other mammalian members of this family, MTGR1 and MTG16 (Kitabayashi et al, 1998a;Gamou et al, 1998). Importantly, MTG16 was identi®ed as a target of the AML-associated t(16;21) translocation, which links this gene to AML1, producing an AML1-MTG16 fusion protein whose structure is similar to AML1-ETO (Gamou et al, 1998). Identi®cation of a second ETO family member involved in a translocation with AML1 suggests that ETO sequences are critical for the transforming activity of these fusion oncoproteins.…”
Section: Eto: a Putative Transcriptional Regulatormentioning
confidence: 99%
“…Besides its involvement in RUNX1-associated t(8;21), RUNX1 has been found to fuse with many partner genes (12) including TEL at 12p13 in B-lineage acute lymphoblastic leukemia (ALL) (13,14) and MDS1 ⁄ EVI1 ⁄ EAP at 3q26 in therapy-related acute myeloid leukemia and myelodysplastic syndrome (t-AML ⁄ MDS) and blast crisis of chronic myelogenous leukemia (15,16). Furthermore, other rare partners have been described previously, including MTG16 (16q24) (17), AMP19(19q13) (18), Copine VIII (12q12) (19), FGA7 (4q28) (20), PRDX4 (Xp22) (21), FOG (Xp22.3) (22),…”
mentioning
confidence: 99%